Choline-deficient High-fat Diet-induced Steatohepatitis in BALB/c Mice - Saut Horas Hatoguan Nababan; Seruni Tyas Khairunissa; Erni Erfan; Nafrialdi Nafrialdi; Ening Krisnuhoni; Irsan Hasan; Rino Alvani Gani (Cell and BioPharmaceutical Institute, 2021)
Background: Non-alcoholic steatohepatitis (NASH) is an expanding cause of chronic liver disease worldwide, including Indonesia, with higher risk progression to cirrhosis and hepatocellular carcinoma. Preclinical experiments using several mice models have been conducted to clarify its complex pathogenesis. This study was designed to investigate whether BALB/c mice on a choline-deficient high-fat diet can be used as a model for NASH. Materials and Methods: BALB/c male mice were fed choline-deficient L-amino acid-defined high-fat diet (CDAHFD) or a standard diet for six weeks. The body and liver weights, liver histology, and plasma biochemistry were analyzed. The relative expression levels of tumor necrosis factor (TNF)α, transforming growth factor (TGF)β1, collagen-1α1 (COL1α1), glutathione peroxidase 1 (GPx1), and uncoupling protein 2 (UCP2) genes in the livers were analyzed using a two-step real time-polymerase chain reaction. Liver fatty acids composition was analyzed using gas chromatography with flame ionization detector (GC-FID). Results: CDAHFD induced steatohepatitis in BALB/c mice with increased plasma levels of alanine aminotransferase. The liver of CDAHFD-fed BALB/c mice showed upregulated relative expression levels of TNFα, TGFβ1, COL1α1, GPx1, and UCP2 genes. The liver fatty acid analysis showed a significant accumulation of saturated fatty acids (SFAs) and an increased ratio of n-6/n-3 polyunsaturated fatty acids (PUFAs) in the livers of CDAHFD-fed BALB/c mice. Conclusion: This study suggests that CDAHFD can induce steatohepatitis in BALB/c mice and therefore may be used as NASH mice model.Keywords: steatohepatitis, fatty liver, choline-deficient high fat diet, BALB/c